PENGARUH PUPUK HAYATI CAIR DAN JARAK TANAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG TANAH ( Arachis hypogaea L. ) VARIETAS TALAM 1 - Asep Kurnia; Amran Jaenudin; Iman Sungkawa (Agroswagati Jurnal Agronomi, 2019)
This study aimed to: (1) determine the effect of the interaction between liquid biofertilizer  and plant spacing on growth and yield of peanut (Arachis hypogea L.) varieties Talam 1, (2) determine the concentration of liquid biofertilizer that gives effect the best on the growth and yield of peanut (Arachis hypogea L.) varieties Talam 1, and  (3) determine the relationship between growth and yield components of peanut (Arachis hypogea L.) varieties Talam 1. The experiment was conducted from April until July 2018 at Sangkanurip Village, Cigandamekar District, Kuningan Regency. Located at a hight of 434,2 m above sea level.The method used in this study is the experimental method. The experimental design used was a randomized block design (RBD) factorial. The study consisted of two treatment factors, is the dose of biofertilizer concentration and the plant spacing repeated three times. The first factor, namely the concentration liquid biofertilizer consists of four levels, namely: K1 (concentration 0 ml / 1 liter of water) K2 (concentration 5 ml / 1 liter of water) K3 (concentration 10 ml / 1 liter of water) K4 (concentration 15 ml / 1 liter of water). The second factor is a spacing (J) consists of three levels, namely: J1 (30 x 15 cm), J2 (30 x 20 cm), and J3 (30 x 25 cm).The results showed that: (1) there is an interaction between liquid biofertilizer and plant spacing on plant height DAP age 41, fresh pods weight per hill, and the weight of dry pods per plot, (2) The treatment of concentration 10 ml / 1 liter of water (K3) and a spacing of 30 x 20 cm (J2) showed  the best effect on the weight of dry pods each plot which produces 1.43 kg/plot, equivalent to the average yield of 2,33 tons / ha, with assuming  80% effective field, (3) there is a significant correlation between plant height age 31, 41 DAP, number of leaves age 21, 41 DAP, leaf area index, and root volume with the weight of dry pods for each  plot.